2015
DOI: 10.1039/c5ce01379h
|View full text |Cite
|
Sign up to set email alerts
|

In situ synchrotron XRD investigation of the dehydration and high temperature carbonation of Ca(OH)2

Abstract: The dehydration and high temperature carbonation reactions of CaIJOH) 2 are an essential part of a number of existing schemes aiming to apply the thermochemical CaO-CaCO 3 cycle ('Ca Looping') in emerging energy industries such as CO 2 capture, gasification and thermal energy storage. However, the underlying chemical mechanisms are poorly understood and the reaction kinetics exhibit a number of strange features such as the increased thermal stability of CaIJOH) 2 , dubbed "superheating", observed in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The presence of molecular water (1630 cm -1 ) and hydroxyl functionality (3750 -3250 cm -1 ) during direct carbonation (Figure 7b) supports findings (Materic and Smedley, 2011) whereby the carbonation reaction proceeds via an adsorbed water film on the surface. Furthermore, the presence of molecular water on the surface can somewhat confirm previous findings, whereby water molecules departing the Ca(OH)2 lattice act as a liquid-like interface for H 2 O and CO 2 to be exchanged (Materic et al, 2015). The identification of bicarbonate species (Figure 7b & Figure 8) provides further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The presence of molecular water (1630 cm -1 ) and hydroxyl functionality (3750 -3250 cm -1 ) during direct carbonation (Figure 7b) supports findings (Materic and Smedley, 2011) whereby the carbonation reaction proceeds via an adsorbed water film on the surface. Furthermore, the presence of molecular water on the surface can somewhat confirm previous findings, whereby water molecules departing the Ca(OH)2 lattice act as a liquid-like interface for H 2 O and CO 2 to be exchanged (Materic et al, 2015). The identification of bicarbonate species (Figure 7b & Figure 8) provides further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 86%
“…In this work prominent issues surrounding calcium looping are investigated primarily through the use of in-situ FTIR, as has been previously called for to further elucidate the role of molecular water (Materic et al, 2015). It is proposed that the onset of the "slow" regime can be spectroscopically identified through an increase in the integrated intensity of spectral features due to vibrational modes of bulk carbonate, initiated at a lower temperature in the presence of water or hydroxyl groups on the surface of particles; 300°C as compared to 400°C in the absence of water.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it has been suggested that CaO and steam could form Ca­(OH) 2 as an intermediate species, which improves the formation of CaCO 3 . Under typical carbonation conditions (>650 °C) employed for the calcium looping cycle, Ca­(OH) 2 cannot exist stably from a thermodynamic point of view, making this pathway an unlikely reason for the improved CO 2 uptake in the presence of steam . However, for carbonation performed at lower temperatures, e.g., for MgO to MgCO 3 , hydroxide species can be thermodynamically stable and affect the carbonation mechanism on the metal oxide; this is discussed in the following section.…”
Section: Fundamentals Of the Carbonation And Calcination Reactionsmentioning
confidence: 99%